General Perspectives for the Treatment of Atherosclerosis - Gulcan, Hayrettin Ozan; Orhan, Ilkay Erdogan (Bentham Science Publ Ltd, 2021)
Atherosclerosis, a cardiovascular disease, is at the top of the list among the diseases leading to death. Although the biochemical and pathophysiological cascades involved within the development of atherosclerosis have been identified clearly, its nature is quite complex to be treated with a single agent targeting a pathway. Therefore, many natural and synthetic compounds have been suggested for the treatment of the disease. The majority of the drugs employed target one of the single components of the pathological outcomes, resulting in many times less effective and long-term treatments. In most cases, treatment options prevent further worsening of the symptoms rather than a radical treatment. Consequently, the current review has been prepared to focus on the validated and non-validated targets of atherosclerosis as well as the alternative treatment options such as hydroxymethyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors, acyl-CoA cholesterol acyl transferase (ACAT) inhibitors, lipoprotein lipase stimulants, bile acid sequestrants, and some antioxidants. Related to the topic, both synthetic compounds designed employing medicinal chemistry skills and natural molecules becoming more popular in drug development are scrutinized in this mini review.
Keywords: Atherosclerosis; HMG-CoA reductase inhibitors; ACAT inhibitors; lipoprotein lipase stimulants; bile acid sequestrants; inflammation